2016
DOI: 10.18632/oncotarget.12193
|View full text |Cite
|
Sign up to set email alerts
|

Elevated level of Interleukin-35 in colorectal cancer induces conversion of T cells into iTr35 by activating STAT1/STAT3

Abstract: IL-35 is a novel heterodimeric and inhibitory cytokine, composed of interleukin-12 subunit alpha (P35) and Epstein-Barr virus -induced gene 3 (EBI3). IL-35 has been reported to be produced by a range of cell types, especially regulatory T cells, and to exert immunosuppressive effects via the STATx signaling pathway. In this study, we demonstrated that IL-35 expression was elevated in both serum and tumors in patients with colorectal cancer. IL-35 mainly expressed in CD4+ T cells in human colorectal cancer tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 37 publications
1
43
2
Order By: Relevance
“…Interleukin-35 (IL-35) is a newly discovered member of the interleukin family with anti-inflammatory and immune inhibitory effects [7,8]. Recently, it has been demonstrated that IL-35 plays an important role in tumor progression, including lung cancer [9], pancreatic cancer [10], nasopharyngeal carcinoma [11], gastric cancer [12], hepatocellular carcinoma [13][14][15], breast cancer [16,17], renal cell carcinoma [18] and colorectal cancer [19,20]. However, the underlying mechanisms of IL-35 in NSCLC remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Interleukin-35 (IL-35) is a newly discovered member of the interleukin family with anti-inflammatory and immune inhibitory effects [7,8]. Recently, it has been demonstrated that IL-35 plays an important role in tumor progression, including lung cancer [9], pancreatic cancer [10], nasopharyngeal carcinoma [11], gastric cancer [12], hepatocellular carcinoma [13][14][15], breast cancer [16,17], renal cell carcinoma [18] and colorectal cancer [19,20]. However, the underlying mechanisms of IL-35 in NSCLC remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Signaling through IL-35 results in the suppression of Janus kinase/signal transducer and activator of transcription pathway [15,16]. Thus, IL-35 always inhibits T cell proliferation and converts naïve T cells into IL-35secreting induced regulatory T cells [17,18]. Importantly, IL-35 dampens inflammatory process and prevents coronary artery lesion in patients with Kawasaki disease [19].…”
mentioning
confidence: 99%
“…Studies also demonstrated that IL‐35 expression was elevated in both serum and tumors in patients with colorectal cancer. These elevated IL‐35 can suppress T‐cell proliferation and may participate in tumor immunotolerance . However, Zhang et al .…”
Section: Il‐35 and Immune‐related Diseasesmentioning
confidence: 99%
“…These elevated IL-35 can suppress T-cell proliferation and may participate in tumor immunotolerance. 91 endothelial growth factor-induced ANG2 and disturbing ANG2/TIE2 signaling. 93 Conversely, IL-35 produced by tumor cells can promote tumor growth by promoting the recruitment of CD11b + GR1 + myeloid-derived suppressor cells and increase angiogenesis in the tumor microenvironment.…”
Section: Il-35 and Tumorsmentioning
confidence: 99%